Targeting Oxidative Stress, NLRP3 Inflammasome, and Autophagy by Fraxetin to Combat Doxorubicin-Induced Cardiotoxicity - Ahmed M. Kabel; Samir A. Salama; Almokhtar A. Adwas; Remon S. Estfanous (MDPI AG, 2021)
Doxorubicin belongs to the class of anthracycline antibiotics that is widely used in the treatment protocols of a wide range of malignancies. The major deleterious effect of doxorubicin use is the possible occurrence of cardiotoxicity. This study aimed to delineate the possible effects of targeting oxidative stress, NLRP3 inflammasome, and autophagy by fraxetin on doxorubicin-induced cardiac dysfunction in rats. In a model of doxorubicin-induced cardiotoxicity, the effects of different doses of fraxetin were assessed by determination of biochemical, histopathological, immunohistochemical, and electron microscopic changes. Fraxetin, in a dose-dependent manner, was found to have the ability to mitigate the harmful effects of oxidative stress and inflammation on myocardial muscles with significant decrease in NLRP3 inflammasome, augmentation of autophagy, and amelioration of the apoptotic signaling pathways. In addition, fraxetin, in a dose-dependent manner, had the ability to combat the echocardiographic, histopathological, immunohistochemical, and electron microscopic changes induced by doxorubicin in cardiomyocytes. As a result, fraxetin may be put into consideration as a new adjuvant line of therapy on the way to mitigate doxorubicin-induced cardiotoxicity.